PENGEMBANGAN TEKNOLOGI PROSES PENGOLAHAN JARAK PAGAR (PURE JATROPHA OIL) KAPASITAS 6 TON BIJI /HARI - heruhadi, bambang (Badan Pengkajian dan Penerapan Teknologi, 2008)
Jatropha Curcas oil as non edible oil is one alternative part of solution for subsitution fosilfuel becoming a great potential biofuel raw material wich recently very popular and seems to be very promising as a future fuel. The plant can be grown on very poor soils and gives a high everage yield of seeds. The JatrophaCurcas.L plantations can be developed to remote area (villages) as a monoculture or tumpangsari (multiple crops). Energi Technology Center (B2TE), BPPT and Ministry of Research and Technology has design and built an 3 x 6 tonnes sheeds/day Jatropha Curcas pilot plant in Ogan Komering Timur (OKUT), South Sumatera. The plant can be processing 18 ton/day seeds, to be coverred 1500 Ha Jatropha curcas plantitions and Pure Jatropha Oil production (PJO) is around 5900 – 6200 liters/day or 2.094.500 – 2.165.500 litters/year.